The effect of Sandblasting and Laser surface treatment on shear bond strength between zirconia and porcelain veneer - Mohammad Hosain Lotfi Kamran; Mahnaz Hatami; Abbas Fallah Tafti; Mohammad Malekzadeh (Tehran University of Medical Sciences, 2017)
Background and Aims: To create a good adhesion between porcelain veneers and zirconia restorations has been important issues is the prosthesis. The aim of this study was to identify an effective way to prepare the zirconia surface infrastructure to increase its shear bond strength to the porcelain veneer. Materials and Methods: 75 samples of zirconia (Y-TZP) cylinders (diameter of 7 mm and a thickness of 3 mm) were fabricated. Based on the surface treatment, specimens were randomly divided into 3 groups: control, air abrasion and Er-YAG laser. After surface treatment, the specimen surfaces were examined by SEM. Using a metal mold, the porcelain was veneered on the zirconia surface and then fired. After thermocycling, the shear bond strength of porcelain to zirconia was measured and then the failure mode of each specimen was analyzed using a stereo-microscope. Data were analyzed by one-way ANOVA and Tukey test. Results: Significant differences were observed between the mean shear bond strength of different groups (P=0.001). The greatest amount of shear bond strength was observed in the group (S) and the lowest bond strength in the control group. Analysis of failure modes showed no statistically significant difference in the type of failure among study groups. The adhesive failure was predominating failure at the intersection of porcelain veneers. Conclusion: The highest shear bond strength between zirconia and porcelain was achieved by sandblasting the zirconia surfaces compare with that of Er_YAG application.